Essential developmental biology - Slack, J. M. W. (Jonathan Michael Wyndham) 1949-; Dale, Leslie (John Wiley & Sons Ltd., 2022)
"This book presents the basic concepts and facts relating to the developmental biology of animals. It is designed as a core text for undergraduate courses from the first to the fourth year, and also for first year graduate students. It is suitable for both biologically based and medically oriented courses. A basic knowledge of cell and molecular biology is assumed, but no prior knowledge of development, animal structure, or histology should be necessary For this, the fourth edition, the work has two authors. Leslie Dale runs the developmental biology teaching at University College London and has brought his invaluable teaching experience as well as his daily contact with cutting edge research to complement the expertise of the senior author, Jonathan Slack. Two technical advances in particular have been incorporated into the text. The first is single cell transcriptome sequencing which provides a completely new way to observe developmental fate and commitment at a molecular level. The second is CRISPR/Cas9, and other methods for targeted genetic manipulation, that have hugely extended the range of what can be done. The book is arranged in four sections and the order of topics is intended to represent a logical progression. The first section introduces the basic concepts and techniques. Chapter 2 "How Development Works" is intended as a very brief summary of developmental mechanisms suitable for introductory lectures. We have moved the biochemistry of signaling systems, formerly in the appendix, into Chapter 4. So now the theoretical concepts of experimental embryology are presented together with the molecular pathways that underlie them. Section 1 also contains a new chapter on "Cells into Tissues" dealing with the fundamentals of morphogenesis and the underpinning role of cell contacts and the cytoskeleton. In other works, this topic is often fragmented among many individual examples and loses its coherence"--Provided by publisher.